2000
DOI: 10.1103/physrevb.62.r13290
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen exchange and transport in thin zirconia films on Si(100)

Abstract: The composition and atomic depth distributions of ultrathin zirconia films (ϳ30 Å ) deposited on Si͑100͒ have been investigated using medium-energy ion scattering ͑MEIS͒. Reoxidation in 18 O 2 permits the oxygen incorporation, exchange, and mobility to be followed due to the isotope sensitivity of the MEIS technique. These quantitative studies showed that significant interfacial SiO 2 growth results when reoxidizing samples at temperatures as low as 500°C, and that this growth saturates in time and pressure bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
63
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(70 citation statements)
references
References 13 publications
5
63
1
Order By: Relevance
“…11 The HfO 2 deposition has therefore catalyzed the oxidation at the interface between the silicon substrate and the chemically stable ultra thin thermally grown oxide. This increase in interfacial oxide thickness with high-k deposition has previously been observed in a number of studies [12][13][14] and has been identified as forming in the initial phase of deposition. The likely cause of this interfacial oxide growth at room temperature is the enhanced dissociation of O 2 into atomic oxygen in the presence of hafnium atoms due to the metal atom catalytic effect.…”
supporting
confidence: 72%
“…11 The HfO 2 deposition has therefore catalyzed the oxidation at the interface between the silicon substrate and the chemically stable ultra thin thermally grown oxide. This increase in interfacial oxide thickness with high-k deposition has previously been observed in a number of studies [12][13][14] and has been identified as forming in the initial phase of deposition. The likely cause of this interfacial oxide growth at room temperature is the enhanced dissociation of O 2 into atomic oxygen in the presence of hafnium atoms due to the metal atom catalytic effect.…”
supporting
confidence: 72%
“…Interfacial silicides form under reducing conditions [3][4][5]15,16], while silicate layers are often observed at interfaces between Si and rare-earth or related oxides. While the experimental conditions under which these layers form are relatively well understood, significant disparity exists in the literature with respect to the reactions causing the formation of interfacial layers, in particular the silicides [4][5][6][7][8][9]17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Postgrowth oxidation in 18 O 2 (98% isotopically enriched) was performed in-situ in the UHV chamber (p base ~10 -9 Torr) connected to the MEIS analysis chamber. The sample was first stabilized at a temperature in the ~ 763 -1223K range (measured by an optical pyrometer and or a K-type thermocouple), followed by 18 31 which is close to the maximum stopping power for protons in Si. Depth profiles of all elements were obtained using a computer simulation code of the backscattered ion energy distributions developed by T. Nishimura.…”
Section: Methodsmentioning
confidence: 99%